Association Between Current Physical Activity and Current Perceived Anxiety and Mood in the Initial Phase of COVID-19 Confinement - López-Bueno, Rubén; Calatayud, Joaquín; Ezzatvar, Yasmin; Casajús, José A.; Smith, Lee; Andersen, Lars L.; López-Sánchez, Guillermo F. (Frontiers in Psychiatry, 2020)
The World Health Organization (WHO) has declared a world pandemic due to COVID-19, and several enacted measures such as compulsory confinement may have collateral consequences on both physical and mental health. We aimed to investigate associations between current physical activity (PA) and current perceived anxiety and mood among a sample of Spanish adults confined due to COVID-19 restrictions of movement. Using an online survey, we collected data on the Spanish adult population regarding health habits during the first days of enacted confinement. A total of 2250 participants (54.8% women) aged 35.3 (SD 13.6) completed the survey, which included questions about sociodemographic characteristics (i.e. age, gender, civil status, education, and occupation), health habits (i.e. prior PA, alcohol consumption, smoking, screen exposure, and sleep hours) and COVID-19 confinement context (i.e. number of isolation days, solitude, and exposure to COVID-19). Physical Activity Vital Sign (PAVS) short form was used to estimate weekly minutes of PA, whereas a single-item question was used to assess both current perceived anxiety and mood. We conducted weighted binomial logistic regressions to check associations between current adherence to WHO guidelines of PA and current perceived anxiety and mood of confined adults. Significant inverse associations between overall adherence to PA and current perceived anxiety in the final adjusted model (OR 0.66; 95%IC: 0.54-0.79) as well as in several subgroup analyses such as younger women were observed. In addition, a borderline significant inverse association was found between current PA and current perceived worse mood when fully adjusted (OR 0.82; 95%IC 0.68-1.00); this association was significantly stronger in women than men. The results of the present study indicate that current PA adherence to WHO guidelines in the initial phase of COVID-19 confinement associates with both lower current perceived anxiety and lower current perceived worse mood among a sample of Spanish adults.